ANALISIS WACANA KRITIS SARA MILLS DALAM VIDEO KLIP MUSIK DESPACITO KARYA LUIS FONSI - Ayunindya Annistri; Mohammad Syahriar Sugandi (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
The rapid technological developments bring up a new era of media information which can be obtained via the Internet, such Youtube. Audiences can watch various categories of information, such as video clips which is a part of the entertainment content contained on Youtube. Video clip is a collection of moving images of the recorded video in order to convey a message and as a promotional tool. One of the video clips from a popular song that has been trending topic throughout 2017 is a video by Luis Fonsi, Despacito. Despacito music video clip has ever been a controversy due to the lyric of the song that invites women to make love. Not only from the audio, the visualization of the video clip also shows a group of women dancing in which they shows their body parts. The research method used in this study is a qualitative research method and critical paradigm. Data analysis used in this research is critical discourse analysis of Sara Mills that uses subject-object position and readers position analysis. The aim of the research is to find out how the subject-object and the audience position in describing the women body on Despacito music video clip. The result of the study shows that women and their bodies are shown in the video clip is a selling object to increase popularity through visualization and audio on the video clip.